2009
DOI: 10.1007/s10661-009-1262-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of heavy metals in sediments and Manila clams Ruditapes philippinarum from Jiaozhou Bay, China

Abstract: Manila clams (Ruditapes philippinarum) and sediments were collected bimonthly during 2007 at five locations in Jiaozhou Bay near Qingdao, China, to determine heavy metal concentrations and to assess the validation of R. philippinarum as a metal biomonitor. Concentrations of heavy metals in clam soft tissues ranged between 0.75 and 3.31, 0.89 and 15.20, 5.70 and 26.03, 52.12 and 110.33, 10.30 and 72.34, 9.64 and 28.60, and 3.15 and 52.75 μg g(-1) dry weight for Cd, Pb, Cu, Zn, Mn, Cr, and Ni, respectively. Most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Samples were sealed in clean polyethylene bags and transferred to the laboratory for immediate storage in a cryogenic freezer (À80 C). Samples were freeze-dried and ground to pass a 150-mesh screen (Wang et al, 2010). All samples were quartered to provide representative sub-samples for further physicochemical analysis.…”
Section: Sediment Sampling and Analytical Methodsmentioning
confidence: 99%
“…Samples were sealed in clean polyethylene bags and transferred to the laboratory for immediate storage in a cryogenic freezer (À80 C). Samples were freeze-dried and ground to pass a 150-mesh screen (Wang et al, 2010). All samples were quartered to provide representative sub-samples for further physicochemical analysis.…”
Section: Sediment Sampling and Analytical Methodsmentioning
confidence: 99%
“…Clam farming, particularly along the northern coast of China, has become an important component of the marine fishery industry [17]. The production of this species has reached levels of over 3.0 million tons per annum in China, which accounts for approximately 70% of mudflat fishery production and 90% of total World production [18]. Furthermore, they are also widely used as sentinel species for monitoring the quality of estuarine and coastal waters.…”
Section: Introductionmentioning
confidence: 99%
“…Some elemental levels in R. philippinarum were compared with those reported previously in these geographical areas without classification purpose. The concentrations of Cu, Zn, Mn, Cd, and Ni in R. philippinarum collected in Jiaozhou Bay were analyzed by Li et al (2006) and Wang et al (2010). Zhao et al (2013b) determined the contents of Cu, Zn, and Cd in R. philippinarum from Deer Island which is close to the sampling sites in Dalian coast in this study.…”
Section: Elemental Concentrations In R Philippinarummentioning
confidence: 91%
“…The seven key variables (Mg, Cd, Sn, Sb, Cs, Ba, and U) selected to differentiate the geographical origins of clams in this study may be related to the surrounding sediments and seawater. Both Wang et al (2010) and Zhao et al (2012) found a statistically significant correlation (p < 0.05) between the concentration of Cd in Manila clam (R. philippinarum) and in surface sediments. Cd concentration in green-lipped mussel and oysters is also significantly correlated to its concentration in sediments (Chaharlang et al 2012;Yap et al 2002).…”
Section: Stepwise Linear Discriminant Analysismentioning
confidence: 95%
See 1 more Smart Citation